Analysis of the effect of air temperature on ammonia emission from band application of slurry. (1st August 2021) - Pedersen, Johanna; Nyord, Tavs; Feilberg, Anders; Labouriau, Rodrigo
Abstract: Field application of liquid animal manure (slurry) is a significant source of ammonia (NH3 ) emission to the atmosphere. It is well supported by theory and previous studies that air temperature effects NH3 flux from field applied slurry. The objectives of this study was to statistically model the response of temperature at the time of application on cumulative NH3 emission. Data from 19 experiments measured with the same system of dynamic chambers and online measurements were included. A generalized additive model allowing to represent non-linear functional dependences of the emission on the temperature revealed that a positive response of the cumulative NH3 emission on the temperature at the time of application up to a temperature of approximately 14 °C. Above that, the temperature effect is insignificant. Average temperature over the measuring period was not found to carry any additional information on the cumulative NH3 emission. The lack of emission response on temperature above a certain point is assumed to be caused by drying out of the slurry and possible crust formation. This effect is hypothesized to create a physical barrier that reduce diffusion of NH3 to the soil surface, thereby lowering the emission rate. Furthermore, the effect of the interaction between soil type and application technique and the effect of dry matter content of the slurry was derived from the model, and found to be significant on cumulative NH3 emission predictions. Graphical abstract: Image 1 Highlights: Air temperature at application is a significant parameter for NH3 emission. Effect of air temperature on NH3 emission is modelled with data from 19 experiments. Cumulative NH3 emission depends non-linearly on air temperature at application. Drying out of the slurry surface is hypothesized to cause non-linear response. Soil type and application technique interactions effect NH3 emission. Abstract : An analysis of NH3 emission data from 19 different experiments measured with the same system was performed to evaluate effect of temperature, which was found to be non-linear.